A National Survey of the Sexual Trauma Experiences of Catholic Nuns - Chibnall, John T. (Review of religious research, 1998)
Much of the research on sexual trauma and religion has focused on male clergy perpetrators and child sexual abuse. In response to this limitation, we conducted a national survey of sexual trauma among Catholic nuns. Sexual trauma was not uncommon, both across the lifespan and during religious life. Childhood sexual abuse was most prevalent (although lower than in the general population), followed by sexual exploitation (primarily by priests and nuns), sexual harassment within the religious community (exclusively by nuns), and sexual harassment at work (primarily by men, both clergy and lay). Past and current sequelae of the trauma included psychological and spiritual dysfunction. Childhood sexual abuse consistently predicted sexual re-victimization in adulthood. The severity of the abuse, age of the victim, and gender and religious status of the abuser modified victims' reactions to and willingness to discuss the trauma. These findings have implications for education, intervention, and policy in religious communities with respect to sexual trauma, and may prove useful to health professionals who treat abused women.